2005
DOI: 10.1016/j.nuclphysa.2004.12.039
|View full text |Cite
|
Sign up to set email alerts
|

The NN final-state interaction in the helicity structure of reaction

Abstract: The influence of final-state N N -rescattering on the helicity structure of the γ d → π − pp reaction in the energy range from π-threshold up to 550 MeV has been investigated. The differential polarized cross-section difference for the parallel and antiparallel helicity states is predicted and compared with recent experimental data. It is shown that the effect of N N -rescattering is much less important in the polarized differential cross-section difference than in the previously studied unpolarized differenti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 25 publications
0
15
2
Order By: Relevance
“…Moreover, this statement is in contradiction to Ref. [10], where a nonvanishing differential spin asymmetry for circularly polarized photons is reported, because this asymmetry is proportional to the beam-target asymmetry T c 10 for circularly polarized photons and a vector polarized deuteron, which means that the latter does not vanish. Thus, it is obvious that the importance of polarization effects requires a more careful and thorough treatment as done in Refs.…”
Section: Introductioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Moreover, this statement is in contradiction to Ref. [10], where a nonvanishing differential spin asymmetry for circularly polarized photons is reported, because this asymmetry is proportional to the beam-target asymmetry T c 10 for circularly polarized photons and a vector polarized deuteron, which means that the latter does not vanish. Thus, it is obvious that the importance of polarization effects requires a more careful and thorough treatment as done in Refs.…”
Section: Introductioncontrasting
confidence: 93%
“…It appears that this fact was not taken into account so that the results in Refs. [9,10] for them cannot be trusted. But also the results for circularly polarized photons are incorrect, namely the claim in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The helicity dependence of the d( γ , π − )pp reaction channel was investigated in Ref. [11] with just the inclusion of NN rescattering in the final state. In that work, the differential polarized cross-section difference for parallel and antiparallel helicity states was predicted and the contribution of the d( γ , π − )pp channel to the deuteron spin asymmetry was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the effects of final state interactions (FSI) are larger in the asymmetry than in the unpolarized cross sections, which leads to a sizeable reduction of the deuteron spin asymmetry in the position of the peak. Both approaches [10,11] were restricted to the (1232)-resonance region in view of a relatively simple elementary pion photoproduction operator based on an effective Lagrangian approach from Ref. [13] that included only Born terms and the (1232) resonance.…”
Section: Introductionmentioning
confidence: 99%